Understanding People’s Relationship With Wildlife in Trans-Himalayan Folklore - Bhatia, Saloni; Suryawanshi, Kulbhushansingh; Redpath, Stephen Mark; Namgail, Stanzin; Mishra, Charudutt (Frontiers in Environmental Science, 2021)
People’s views and values for wildlife are influenced by the ecology of the species and the type of interaction between them. Local folklore provides a resource that can enable us to better understand these interactions and the underlying cultural values. Using archival searches and semi-structured interviews, we collected narratives about the ibex Capra sibirica (n=69), and its predators, wolves Canis lupus (n=52) and snow leopards Panthera uncia (n=43), in Ladakh, India. We compared these stories to those of a mythical carnivore called seng ge or snow lion (n=19), frequently referenced in local Tibetan Buddhist folklore and believed to share many of the traits commonly associated with snow leopards (except for livestock depredation). We then categorized the values along social-cultural and psychological dimensions and found that the ibex was predominantly associated with utilitarianism and positive symbolism. Both snow leopard and wolf narratives referenced negative affective and negative symbolic values, though more frequently in the case of wolves. Snow leopard narratives largely focused on utilitarian and ecologistic values. In contrast, snow lion narratives were mostly associated with positive symbolism. Our results suggest that especially for snow leopards and wolves, any potentially positive symbolic associations appeared to be overwhelmed by negative sentiments because of their tendency to prey on livestock, unlike in the case of the snow lion. Since these values reflect people’s real and multifarious interactions with wildlife, we recommend paying greater attention to understanding the overlaps between natural and cultural heritage conservation to facilitate human-wildlife coexistence.